Uma análise situacional das contribuições do método terapia ocupacional dinâmica para inserção social de crianças autistas - Cestari , Leila Maria Quiles (2024)
The Development of the Dynamic Occupational Therapy Method (MTOD) began in the 1970s with occupational therapist Jô Benetton. The care provided under the principles of the MTOD occurs through its unique and continuous concepts and processes: constructing the situational diagnosis, managing the dynamics of the triadic relationship, conducting dialogical evaluations to build meaning, and expanding health spaces in daily life. Its ultimate goal is the social inclusion of the target individual.Care for autistic children is immersed in contemporary tensions, incorporating practices centered on addressing deficits and normalizing behaviors for social interaction, advocacy movements by autistic individuals promoting the neurodiversity perspective, education and healthcare institutions, and issues of profitability. The MTOD aims to support occupational therapists’ practice by moving away from the medical and rehabilitative paradigm, establishing a singular, non-protocol-driven approach guided by the needs, desires, and strengths of the target individual within the complexities and contingencies of their situation.To describe processes that highlight the contributions of MTOD to the social inclusion of autistic children, this research adopts a qualitative, exploratory-descriptive design using the methodology of Situational Analysis (SA). Participants included three occupational therapists with at least five years of clinical training in MTOD, two children receiving therapy from these occupational therapists, and one adult who had received therapy as a child, along with their families and team members identified as relevant for understanding aspects of social inclusion.Data were collected through interviews using semi-structured guides for occupational therapists and open-ended questions for family members and team members. Additionally, creative methodologies were employed with the children, including photography, augmentative and alternative communication resources, and the associative trails technique. Data were analyzed through SA, generating three types of maps: situational, social world/arena, and positional maps.The results integrated the constructed maps and the human actors' discourse, culminating in the following categories: the meeting with the occupational therapist, situational diagnosis, management of the triadic relationship, the setting, the "fourth term," the construction and expansion of health spaces, the building of meanings, and MTOD with autistic individuals. It was observed that the children initially had restricted activity repertoires and interests focused on hyperfixations. Occupational therapists began expanding and constructing health spaces based on these interests, introducing new activity possibilities aligned with the child’s desires, fostering an affective relationship through positive transference. Expansions initiated in the occupational therapy setting, deemed significant by the individuals and their families, extended into health spaces within their daily lives, supported by key adults, thereby promoting social inclusion in an ethical and aesthetic manner.This research reveals a form of care for autistic children that aligns with their own desires: an intervention rooted in respect and a thoughtful understanding of individual needs, rejecting fragmented practices that address only isolated aspects. The study discusses limitations, particularly regarding intersectional issues, and suggests directions for future research.We hope to expand dialogues, reflections, and knowledge about treatment possibilities for autistic children, contributing to professional and academic advancements in occupational therapy. Additionally, we aim to foster necessary transformations in care practices for children, reflecting their contextual needs and desires.